Mechanical technology - Bacon, D. H. [ (Dennis Henry)]; Stephens, R. C. [ (Richard Courtney)] (Butterworth-Heinemann, 1998)
Almost encyclopedic in scope, this comprehensive one volume source will be an essential reference for any engineer's library. It combines concise coverage of mechanical engineering principles with illustrative worked-out examples